floprovides
floprovides
01-09-2017
Mathematics
contestada
g(x)= 3x − 3; Find g(−6)
Respuesta :
wikk
wikk
01-09-2017
g(x)= 3x − 3
g(−6)
g(-6) = 3(-6) - 3
g(-6) = -18 - 3
g(-6) = -21
The answer is -21.
Answer Link
choixongdong
choixongdong
01-09-2017
g(−6) =
3(-6) − 3 = -18 - 3 = -21
answer
g(−6) = -21
Answer Link
VER TODAS LAS RESPUESTAS ( 74+ )
Otras preguntas
How many solutions does this system have? y = 5x + 6 y – 5x = 7 A. no solutions B. 1 solution C. 2 solutions D. infinitely many solutions
What is Colorado state sales tax?
The term of office for constitutional court judges is determined by a. the Constitution. b. Congress. c. the Department of Justice. d. the President. Pl
What is the number of ways to arrange 8 object from a set of 12 different objects?
Monisha decides to join a gym for a minimum of one month to train for a triathlon. The gym charges a joining fee of $100 and a monthly fee of $37. If x represen
Suppose the half-life of element k is 20 minutes. if you have a 200 g sample of k, how much of element k will be left after 60 minutes? (do not use significant
Five-year-old twins wyatt and adam both want to play with the same toy car. after squabbling for a bit, wyatt picks up the car and bashes his brother over the h
A set data has a line of best fit of y=2.5-1.5 What is the residual for the points (4,7) A,B,C,D in pic
1. How can exclude aid in the relief stress? 2. Why is the development of motor skill essential? 3. Why are skills and game knowledge important to participate i
What is the best way to be sure that you get the nutrients essential for good health? a. Keep a daily journal of what you eat. b. Be sure to eat selections from